Climate change and maize production, and potential adaptation measures: a case study in Jilin Province, China - Wang, M.; Li, Y.; Ye, W.; Bornman, Janet; Yan, X. (Inter-Research, 2011)
Jilin is among the most important grain-producing provinces in China. Its maize productionplays an important role in local and national food security. In this study, we developed a newapproach to assess the vulnerability and adaptation options for Jilin maize yields with respect toclimate change by modifying a site-based biophysical model to a spatial grid-based application. Anensemble approach that used a combination of 20 general circulation model results and 6 scenariosfrom the Special Report on Emissions Scenarios was adopted in order to reflect the high uncertaintiesin future climate projections. The results show that the yield is highly likely to decline in the westernand central regions of Jilin but to increase in the east, where maize is not currently grown as the maincrop. Phenologically, the growing season will be reduced in the central and western parts, leading toa shortened grain-filling period. The average maize yield in the west and central regions is thus projectedto decrease 15% or more by 2050 as predicted by 90% of 120 projected scenarios. In addition, CO2 fertilization was investigated and demonstrated a noticeable compensation effect on the yield deduction. However, further field work and/or laboratory-based experiments are required to validatethe modeled CO2 fertilization effects. Two potential adaptation strategies, i.e. improving irrigationfacilities and introducing cultivars, were identified from the vulnerability assessment and were furthertested for the reduction areas. The results revealed that the increase in effective irrigation by upgrading the irrigation system would help to maintain the current production level, but in the long run, the maize cultivars need to be introduced in line with the future warming climate.